Open-shell singlet diradicaloid difluoreno[4, 3-b:3′, 4′-d]furan and its radical cation and dianion. Issue 44 (1st May 2020) - Mori, Sakura; Akita, Motoko; Suzuki, Shuichi; Asano, Motoko S.; Murata, Michihisa; Akiyama, Tsuyoshi; Matsumoto, Taisuke; Kitamura, Chitoshi; Kato, Shin-ichiro
Abstract : We report difluoreno[4, 3- b :3′, 4′- d ]furan derivative as a stable open-shell singlet diradicaloid. Abstract : Difluoreno[4, 3- b :3′, 4′- d ]furan (DFFu) was prepared via a short, scalable, multi-step synthesis, and characterized by crystallography, spectroscopic measurements, and theoretical calculations. Even though the results revealed an open-shell singlet diradical character, DFFu is stable under ambient conditions. The radical cationic and dianionic species of DFFu were also synthesized and characterized.